2000
DOI: 10.1111/j.1574-6968.2000.tb09096.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Staphylococcus aureus induces apoptosis in mouse osteoblasts

Abstract: Staphylococcus aureus invades osteoblasts and is the primary cause of osteomyelitis. This study examined the ability of S. aureus to induce apoptosis in a mouse osteoblast cell line. The presence of intracellular S. aureus was demonstrated by transmission electron microscopy. Light microscopy was utilized to examine morphological changes in the osteoblasts following killing of extracellular bacteria. Cell rounding was observed, and dark centers due to condensation of chromatin were noted in cells in infected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 20 publications
5
80
1
Order By: Relevance
“…This reduced ERK 1 and 2 phosphorylation observed at the highest MOI used may be attributed to cell death via necrosis and/or apoptosis. We have recently demonstrated that S. aureus does induce osteoblast apoptosis (54). When osteoblasts were pretreated with the MEK 1 and 2 inhibitor PD98059, ERK 1 and 2 phosphorylation was undetectable in infected osteoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced ERK 1 and 2 phosphorylation observed at the highest MOI used may be attributed to cell death via necrosis and/or apoptosis. We have recently demonstrated that S. aureus does induce osteoblast apoptosis (54). When osteoblasts were pretreated with the MEK 1 and 2 inhibitor PD98059, ERK 1 and 2 phosphorylation was undetectable in infected osteoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial cells, keratinocytes, or osteoblasts, S. aureus-induced apoptosis may require internalization of the bacteria (26,27,30,32,33). Conversely, Bantel et al (16) showed that S. aureus α-toxin does not require bacterial internalization to induce apoptosis.…”
Section: Figurementioning
confidence: 99%
“…Induction of apoptosis by S. aureus may cause tissue damage, compromise the antimicrobial immune response, and thereby facilitate bacterial spread. S. aureus can induce apoptosis of epithelial cells (26)(27)(28), endothelial cells (29-31), keratinocytes (32), osteoblasts (33), lymphocytes, and macrophages (34).…”
Section: S Aureus Is One Of the Most Common Gram-positive Bacterial mentioning
confidence: 99%
“…As a-toxin can directly target mitochondria leading to cytochrome c release, 32 one might speculate that a-toxin-induced AIF translocation might be particularly important in those cell types, in which cell death induction may require internalization of S. aureus. [25][26][27][28] In view of the fact that AIF does not exhibit intrinsic DNase activity, the downstream effectors remain obscure. Although several noncaspase proteases such as calpains, serine proteases and cathepsins have been implicated in cell death processes, [48][49][50][51] and even the loading of any type of protease into cells provoked apoptosis-like morphologies, 52 it is presently unknown whether any of these proteases are involved in a-toxin-induced cell death.…”
Section: S Aureus A-toxin Mediates Cell Death Via a Necrotic Pathwaymentioning
confidence: 99%
“…22,23 Indeed, it was shown that S. aureus is able to induce apoptosis in various cell types including epithelial cells, endothelial cells, keratinocytes, osteoblasts as well as lymphocytes and macrophages. [24][25][26][27][28][29] One of the key virulence determinants of S. aureus is a-toxin, a pore-forming protein of 34 kDa. At low doses, the toxin was shown to bind to specific, as yet unidentified cell surface receptors, and to produce small heptameric pores that selectively facilitate the release of monovalent ions, resulting in DNA fragmentation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%